The Relationship between Housing Condition and Pulmonary Tuberculosis Disease in Baraya Village Bontoala Makassar, Indonesia - Syamsuddin S1 , Hamsir Ahmad2 , Wahyuni Sahani3 , Indah D. Lestari4 , M. Askar5 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Objective: This study aims to determine the relationship between the incidence of pulmonary tuberculosiswith housing conditions consist of several factors, such as occupancy density, roomization, ventilation,temperature, humidity, and lighting.Method: This study was observational with a cross-sectional approach. The population in this study was thepatient’s home with pulmonary TB disease in Baraya village, Bontoala sub-district, Makassar. The sampleswere selected by simple random sampling involved 65 houses. Data were analyzed using SPSS for Windowswith the Chi-square test.Result: This research found a significant relationship between pulmonary tuberculosis with occupant density(p=0.000), roomization (p=0.000), ventilation (p=0.000), temperature (p=0.000), and humidity (p=0.001).There is no relationship between lighting exposure (p=0.757) to the incidence of pulmonary tuberculosis.Conclusion: The house condition primarily occupant density, roomization, ventilation, temperature, andhumidity has strongly influenced the occurrence of Tuberculosis in the community, especially in Indonesia,even though lighting exposure statistically not significant.